STRATEGI PENGEMBANGAN KEMAMPUAN PUBLIC SPEAKING DAN DAMPAKNYA TERHADAP LIFE SKILL SANTRI MELALUI KEGIATAN MUHADARAH - Zaidatul Arifah; Sintia; Sholeh Kurniandini (JBI : Jurnal Bahasa Indonesia, 2025)
This study aims to examine the strategies for developing public speaking skills and their impact on the life skills of students (santri) through muhadarah activities at the Manbaul Qur’an Dormitory of MAN Temanggung. Using a descriptive qualitative approach and a case study method, the research found that the strategy for implementing muhadarah activities includes the preparation of a rotating public speaking schedule, tiered assignment of speaking tasks based on participants’ competence levels, improvement of content quality, enhancement of proficiency in four languages (Indonesian, Arabic, English, and Javanese), audience analysis, intensive mentoring during muhadarah sessions, provision of constructive feedback to speakers, and regular activity evaluations. The development of public speaking skills through muhadarah has had a significant impact on students' life skills, particularly in fostering independence, critical thinking, interpersonal communication, adaptability, emotional management, and time management abilities.